Impaired Skeletal Muscle Development and Regeneration in Transglutaminase 2 Knockout Mice - Zsófia Budai (MDPI AG, 2021)
Skeletal muscle regeneration is triggered by local inflammation and is accompanied by phagocytosis of dead cells at the injury site. Efferocytosis regulates the inflammatory program in macrophages by initiating the conversion of their inflammatory phenotype into the healing one. While pro-inflammatory cytokines induce satellite cell proliferation and differentiation into myoblasts, growth factors, such as GDF3, released by healing macrophages drive myoblast fusion and myotube growth. Therefore, improper efferocytosis may lead to impaired muscle regeneration. Transglutaminase 2 (TG2) is a versatile enzyme participating in efferocytosis. Here, we show that TG2 ablation did not alter the skeletal muscle weights or sizes but led to the generation of small size myofibers and to decreased grip force in TG2 null mice. Following cardiotoxin-induced injury, the size of regenerating fibers was smaller, and the myoblast fusion was delayed in the tibialis anterior muscle of TG2 null mice. Loss of TG2 did not affect the efferocytic capacity of muscle macrophages but delayed their conversion to Ly6C−CD206+, GDF3 expressing cells. Finally, TG2 promoted myoblast fusion in differentiating C2C12 myoblasts. These results indicate that TG2 expressed by both macrophages and myoblasts contributes to proper myoblast fusion, and its ablation leads to impaired muscle development and regeneration in mice.